Assessment of Seismic Retrofitting Interventions of a Masonry Palace Using Operational Modal Analysis. Issue 5 (4th May 2022) - Aloisio, Angelo; Di Pasquale, Alessandro; Alaggio, Rocco; Fragiacomo, Massimo
ABSTRACT: The paper delivers a short report about the modal identification carried out on a historical masonry palace in the city centre of L'Aquila, Palazzo Pica Alfieri, retrofitted after the 2009 earthquake. A concise description of the damage pattern and the retrofitting interventions heads the presentation of the results of the dynamic identification using Operational Modal Analysis. The identified mode shapes and natural frequencies drive a discussion about the detectability and the assessment of the modifications induced by the structural interventions using low-vibration measurements. Differently from more uncomplicated structures, the production of a Finite Element model representative of an existing masonry complex requires considerable efforts: the masonry structure may not behave like a continuum, due to the presence of cracks and unknown structural discontinuities. Still, the results of the dynamic identification bestow valuable information about the structural behaviour from a qualitative viewpoint, even if not backed by a faithful FE model. The paper addresses the aspects possibly related to the dynamic identification of a monumental masonry building, based on the shreds of evidence arisen from the presented case study.